Study Of Accessible Public Space For The Elderly Case Study Of Simpang Lima, Semarang City - Anggraini, Dini Silvia; Ikhsani, Muhammad Azmy; Masyitoh, Husnul; Pratama, Hilba Yoga (Talenta Publisher, 2025)
The development of an area cannot be separated from the existence of public space, Public Space such as Simpang Lima is one of the important aspects in city development so that it can be utilized by the community, public space must be usable by all levels of society, including elderly users. Currently, the city of Semarang has experienced an increase in the number of elderly people since 2017 and continues to increase, special attention to elderly users is important so that this increase does not become a new problem in urban areas. One of the government's efforts to pay attention to the elderly is by creating public spaces. Public spaces in the city of Semarang, such as Simpang Lima, are still popular with the elderly. Many elderly people are found in the morning with sports activities, but according to the elderly, the facilities at Simpang Lima have not been able to meet their needs. So that it raises several problems in the field, these problems are the basis of the study, namely What is the accessibility of the elderly in the Simpang Lima public space? What are the obstacles to accessibility for the elderly in using public space facilities at Simpang Lima? The research method uses a qualitative approach by conducting observations, interviews, and literature reviews after which it is analyzed using accessibility requirements. The activities of the elderly in reaching and using public spaces are in accordance with the accessibility that has been provided, this is based on convenience and safety. Accessibility barriers experienced by the elderly at Simpang Lima are the lack of supporting accessibility facilities such as comfortable seating, information boards and directions, and toilets complete with facilities for the elderly.